Internalisasi Nilai Spiritualitas melalui Strategi Pedagogis Guru Tahfidz: Respons terhadap Problematika Kesulitan Menghafal Al-Qur'an pada Murid MA al-Islam Surakarta - Muhammad Shidiq; Joko Subando (Lembaga Yasin AlSys, 2026)
The problems of Qur’an memorization among adolescents constitute a complex pedagogical issue because they involve cognitive, psychological, spiritual, and environmental dimensions that interact with one another. This study aims to analyze the strategies of tahfidz teachers in overcoming difficulties in Qur’an memorization among students at Madrasah Aliyah Al-Islam Surakarta in the 2025/2026 academic year. This study used a descriptive qualitative approach with a case study design. The research subjects consisted of tahfidz teachers as the main informants, as well as Madrasah Aliyah students and madrasah management as supporting informants. Data were collected through semi-structured interviews, non-participatory observation, and documentation analysis, then analyzed using thematic analysis techniques. Data validity was ensured through source and technique triangulation, member checking, and researcher reflexivity. The results showed that the main problems faced by students included low concentration, lack of learning motivation, boredom in muroja’ah, and weak time management between general academic workloads and memorization targets. Tahfidz teachers responded to these problems through adaptive pedagogical strategies, including the integration of the talaqqi, tikrar, tasmi’, and muroja’ah methods, personal approaches and the development of intrinsic motivation, the creation of a conducive learning environment based on spiritual values, and a structured and continuous memorization evaluation system. These findings indicate that the effectiveness of tahfidz teachers’ strategies is influenced by their ability to integrate modern pedagogical approaches with classical Islamic learning traditions. The conclusion of this study emphasizes the importance of integrative, adaptive, and contextual tahfidz learning strategies in overcoming difficulties in Qur’an memorization in formal madrasahs. The contribution of this study lies in strengthening the conceptual model of tahfidz learning that integrates pedagogical, psychological, spiritual, and managerial aspects in Islamic education.